If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5x + -3 = -19 Reorder the terms: -3 + 3x + 5x = -19 Combine like terms: 3x + 5x = 8x -3 + 8x = -19 Solving -3 + 8x = -19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 8x = -19 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = -19 + 3 8x = -19 + 3 Combine like terms: -19 + 3 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 0.2x(x+3)-4(2x-3)=0.9 | | y+258=-8y-3 | | 7.50+2.50b=12.50 | | (4x-12)/7 | | (X+3)2+(6x)=46 | | 7x=-5+2(3x+9) | | S-12=47 | | y-13=0(x-4) | | 4x-12/7 | | -3.8s-6.92=19.96+2.6s | | -2d-9=d+84 | | 16-2x^2=-10 | | 19-15-18z=-16-19z | | -3.62-15.1d=16.78-14.4d+2.3d | | t-67=-2t-7 | | 14z=266 | | 9x^2+15=15 | | 6x=360(24) | | 3(-2x+4)=6(x-2) | | m-1/23/2 | | -20-20u=-13u+19+3 | | C=3.14(14) | | 12x^5y^8/4x^2v^3 | | -5a+6=a+150 | | 2x=35(7) | | (6x-4)+(6x-4)+(2x+10)+(2x+10)=(6x-4)+(6x-4)+(2x+10)+(2x+10) | | y=x+35 | | 18-17m=-13m-6 | | 3(-2x+4)=6(x+2) | | 5w-16=24 | | -y=-3y-14 | | 6x-8x+2=-3 |